The relative importance of methylation and demethylation in rice paddy soil varies depending on the presence of rice plants - Rachel J Strickman; Sarah Larson; Huang Haiyong; Evangelos Kakouros; Mark M D Marvin-DiPasquale; Carl P J Mitchell; Rebecca B Neumann (PANGAEA, 2021)
This data was collected in order to understand the influence of rice plants on methylation and demethylation on methylmercury (MeHg) concentration in rice paddy soil, and to assess which process was more dominant in paddy soil. Soil for the experimental work was collected from the Yolo Bypass, near Sacramento, California, an area with a strong commercial rice growing industry. Experimental work was carried out in growth chambers at the University of Washington. Soil was collected in October 2017 and experimental work was carried out in late 2018-early 2019. We established rice paddy microcosms with and without rice plants (n=6 in each treatment) and maintained them until the planted boxes had reached the peak of vegetative growth. At this time, we amended the soil with stable isotope tracers to measure methylation and demethylation potential rates based on an 8 hour incubation period. From these soil samples, we collected information on soil background (ambient) MeHg, inorganic Hg, total sulfur content, and methylation and demethylation potential rate constants. Information on rice root exudation rates was also collected in an experiment performed in 2019. In brief, the following methods were used for each analysis. Methylmercury concentrations (both ambient and tracer) were measured using using isotope dilution-gas chromatography-ICPMS (Hintelmann et al., 2000). Ambient and tracer THg concentrations were analyzed using isotope dilution-cold vapour-ICPMS. Inorganic Hg was calculated as total Hg minus MeHg. Total sulfur was assessed using EPA-3050 combined with EPA 200.7 on a Thermo-Scientific 6300 ICP spectrometer. Methylation and demethylation potential rate constants were measured using stable isotope tracer and the isotope-dilution method of Hintelmann et al 2000. Rice root exudates were measured from soil-grown plants using the calcium sulfate incubation method of Aulakh et al. (2001).